Positive solutions for a singular fractional boundary value problem. (5th July 2020) - Tudorache, Alexandru; Luca, Rodica
Abstract : We investigate the existence of positive solutions for a system of Riemann‐Liouville fractional differential equations, supplemented with uncoupled nonlocal boundary conditions which contain various fractional derivatives and Riemann‐Stieltjes integrals, and the nonlinearities of the system are nonnegative functions and they may be singular at the time variable. In the proof of our main theorems, we use the Guo‐Krasnosel'skii fixed point theorem.